HIV Disclosure—Professional Body Guidelines, the Law and the Boundaries of Medical Advice. (19th May 2021) - Ryan, Samantha; Phillips, Matt
Abstract: This article examines the current BHIVA/BASHH guidelines on the disclosure of HIV+ status in the context of sexual activity. It assesses whether the guidance provided on how to avoid criminal prosecution accurately reflects the prevailing position in law. Given that aspects of the guidance related to non-disclosure of HIV infection in the context of low or negligible risk are as yet untested in UK law, it is argued that there is some uncertainty as to whether the professional body guidelines and the law can be reconciled with each other. The article also considers whether the BHIVA/BASHH guidelines stray beyond the boundaries of medical advice as normally understood (focused on the protection of health and the prevention of onward transmission), by posing both as legal advice on how to avoid prosecution and offering what could be viewed as a moral judgement as to when disclosure is required. While a bio-medical assessment of risk naturally shapes clinical guidelines and may also inform views as to appropriate sexual behaviour and risk-taking, it is unclear whether scientific assessment of risk should be the sole guide when it comes to determining the nature of any disclosure obligation or the medical advice to be given on this matter.